Learning Media Improves Achievement Learning Science of Fourth Grade Elementary School Students - Nadrah, Nadrah (Universitas Pendidikan Ganesha, 2023)
At present, teachers need to pay more attention to the use of learning media in carrying out learning activities. This research aimed to maximize the level of science learning achievement of fourth graders taught using instructional media and analyze the use of instructional media on science learning achievement in fourth graders of elementary school. This study uses an experimental approach with a comparative design. The population, as well as the sample of this study, amounted to 80 grade IV SD students. Methods of data collection using documentation and test techniques. The data collection instrument used questionnaires and test sheets. The data analysis technique used is a descriptive and inferential statistical analysis using the t-test formula. The results obtained are that the level after learning is generally in the lower category. In the experimental group, before learning was generally in the less category, and after learning increased to be quite good. The conclusion from this study is that there is a positive impact of the use of instructional media on student performance. Groups of students who were given learning using media were more likely to show an increase in learning performance compared to students who were taught not to use learning media.